Search for Down-Type Fourth Generation Quarks with the ATLAS Detector in Events with One Lepton and Hadronically Decaying W Bosons - Onofre, A. (2012)
This Letter presents a search for pair production of heavy down-type quarks decaying via b′→Wt in the lepton+jets channel, as b′¯b′→W−tW+¯t→b¯bW+W−W+W−→l±νb¯bq¯qq¯qq¯q. In addition to requiring exactly one lepton, large missing transverse momentum, and at least six jets, the invariant mass of nearby jet pairs is used to identify high transverse momentum W bosons. In data corresponding to an integrated luminosity of 1.04  fb−1 from pp collisions at √s=7  TeV recorded with the ATLAS detector, a heavy down-type quark with mass less than 480 GeV can be excluded at the 95% confidence level.